A Comparative Handbook to the Gospels of Matthew and Luke : Comparisons with Pseudepigrapha, the Qumran Scrolls, and Rabbinic Literature - Chilton, Bruce D. (The New Testament Gospels in their Judaic Contexts, 2021)
This Handbook provides any commentator - whose purposes might include writing a consecutive treatment of a Gospel, or engaging with episodic themes or passages, or preparing a particular section of the Gospel for study, teaching, or preaching - with resources from the Gospels' Judaic environment that appear useful for understanding the texts themselves. Translation, presentation, comparison with Judaica, and occasional comments are all designed with that end in view. Materials are included from the Pseudepigrapha (together with Philo and Josephus), discoveries related to Qumran, and Rabbinic Literature (inclusive of the Targumim). As in a previous volume that dealt with Mark's Gospel, this Comparative Handbook targets the issue of comparison more than analysis or commentary.